Increase of secondary mutations may be a drug-resistance mechanism for lung adenocarcinoma after radiation therapy combined with tyrosine kinase inhibitor - Zhuang, Hongqing (J Cancer, 2019)
Objective: To investigate changes in the secondary mutations of tumor in a drug-resistance mechanism for lung adenocarcinoma after radiation therapy combined with tyrosine kinase inhibitor (TKI). Methods: Lung adenocarcinoma cell line PC9 in vitro and xenograft model in nude mice were used to observe tumor inhibitory effects and drug-resistance under the effect of radiation therapy combined with erlotinib through apoptosis detection through in vitro survival curve and in vivo growth curve; changes in gene mutations before and after drug-resistance in nude mice xenografts were observed by the next generation sequencing, and the relationship between cancer drug-resistance and radiation therapy combined with TKI was observed. Results: Radiation therapy combined with erlotinib had a more reliable radio-sensitizing effect in vitro and in vivo, however, there were several drug-resistant tumor cells. Meanwhile, radiation therapy combined with erlotinib could significantly increase the number of mutations in tumor genes. The whole genome sequencing showed that the secondary mutation in the combined treatment group significantly increased in comparison with those of the single treatment group and the blank control group. Conclusion: The increase of secondary mutations may be an important drug-resistance mechanism for lung adenocarcinoma after radiation therapy combined with TKI, which provided further space exploration under the combined action of radiation and TKI.